Comprehensive Characterization of the RNA Editomes in Cancer Development and Progression - Luo, Haitao; Fang, Shuangsang; Sun, Liang; Liu, Zhiyong; Zhao, Yi (Frontiers in Genetics, 2018)
RNA editing is a post-transcriptional event that leads to transcriptome diversity and has been shown to play important roles in tumorigenesis. However, dynamical changes and the functional significance of editing events during different cancer stages have not yet been characterized systematically. In this paper, we describe a comprehensive study of the RNA editome of four samples from different cancer stages for the same patient based on analysis of both whole-genome and transcriptome sequencing data. We identified 35,225 and 33,784 RNA editing events for poly(A)+ and poly(A)- RNA sequencing data respectively in all four samples and show that 93% and 90% correspond to cancer stage-specific editing events. We also found that half of editing sites in 3'UTR of coding genes were microRNA targets and most of the sites in the coding regions could lead to nonsynonymous amino acid changes. Functional analysis of genes which suffered damaging nonsynonymous editing events in each cancer stage show the gradual expansion of cancer related pathways accompanied by an increasing malignant grade of the samples. Our study, for the first time to our knowledge, comprehensively profiled and compared the editomes across the different cancer stages and revealed the functional impacts of RNA editing events during cancer development and progression.